EL ESPLÉNDIDO LEGADO DE TABRIZI MASTERS - Allahverdiyev, Murad (Revista Inclusiones, 2018)
This article tells about the surprisingly bright phenomenon in the world of art – the Islamic medieval miniature which has been represented for centuries by many schools and talented artists.It should be noted that by choosing this topic we wanted to review the Azerbaijani miniature not in the traditional terms of art criticism, but rather by adopting it as a document that illustrates, albeit in a system of special characters and images, many of the important events of the past, gives an idea of how the Azerbaijani masters who lived in the formidable medieval times, what they believed in and how they saw the world at the time of creation and destruction of the most powerful empires of the East.